Comments of the Federal Military Government on the report of the Tribunal of Inquiry into the Affairs of the Nigerian Ports Authority: for the period October 1, 1960 to December 31, 1965. - Nigeria (Lagos : Federal Ministry of Information, Print. Division, 1968)
This reports is a compilation of comments that emanated from the work of a committee set up to investigate acts and activities of the Nigeria port authority, and to provide likable suggestion on how to improve the outcome of the institute.
asm; 06/03/19
Loans
Keywords: Nigerian Ports Authority; Nigeria